Respuesta :
Answer:
[tex]y=-\frac{x-6}{3}[/tex]
Step-by-step explanation:
To find the inverse function, switch the y and x
[tex]y=6-3x[/tex] becomes [tex]x=6-3y[/tex].
Now, rearrange so that the equation is equal to y.
[tex]x=6-3y\\x-6=-3y\\-\frac{x-6}{3} =y[/tex]
Hope this helps!
Answer:
-1/3(x-6)
Step-by-step explanation:
Let y = 6-3x
Exchange x and y
x = 6-3y
Solve for y
Subtract 6 from each side
x-6 = 6-6 -3y
x-6 = -3y
Divide each side by -3
(x-6)/-3 = -3y/-3
-1/3 (x-6) = y
This is the inverse
-1/3(x-6)